Total Dissolved Solids (TDS), Electrical Conductivity (EC), dan pH sebagai Indikasi Awal Keterdapatan Pencemar pada Air - Elsiana, Rima Anisa; Kurniawan, Dinar Hananto (Mataram University, 2025)
Water is highly susceptible to contamination from anthropogenic factors, particularly in river water and shallow groundwater located in densely populated residential areas such as the study site. The research area is situated around the Winongo River, covering parts of Tegalrejo, Pringgokusuman, Pakuncen, and Ngampilan sub-districts in Yogyakarta City, D.I.Y. Studies on water quality are generally conducted through field measurements and water sampling. However, when water sampling is not carried out simultaneously with field measurements, the process becomes inefficient and increases the risk of laboratory test results not accurately representing actual environmental conditions. Therefore, this study aims to demonstrate that Total Dissolved Solids (TDS), Electrical Conductivity (EC), and pH can serve as preliminary indicators of the presence of pollutants, particularly ionic contaminants. The analysis was conducted through qualitative correlation using mapping and quantitative correlation between pH, TDS, and EC with nitrate concentration using Spearman’s correlation test. The results show that TDS and EC exhibit a strong correlation with nitrate levels. This is because nitrate is highly soluble and consists of ionic bonds that can move freely in solution. In contrast, pH also shows a correlation with nitrate but not as strong as TDS and EC, since pH does not directly detect nitrate ions. Therefore, TDS and EC can be effectively used as early indicators of contamination, especially for pollutants containing ionic bonds.